2000
DOI: 10.1590/s0036-46652000000200008
|View full text |Cite
|
Sign up to set email alerts
|

Chromobacterium violaceum infection in Brazil. A case report

Abstract: We report the second case of infection with Chromobacterium violaceum that occurred in Brazil. A farm worker living in the State of São Paulo presented fever and severe abdominal pain for four days. At hospitalization the patient was in a toxemic state and had a distended and painful abdomen. Chest X-ray and abdominal ultrasound revealed bilateral pneumonia and hypoechoic areas in the liver. The patient developed failure of multiple organs and died a few hours later. Blood culture led to isolation of C. violac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 10 publications
3
21
0
6
Order By: Relevance
“…The clinical manifestations of chromobacteriosis begin after the incubation period ranging from 3 to 14 days, according to the form of exposure to the agent [1,8]. It includes inflammatory signs at the entry site, associated with fever, nausea, vomiting, abdominal pain [1,3,4] with rapid evolution to sepsis, rapid spread and high mortality [2,3,12,13]. There is formation of multiple abscesses in the lung, liver, spleen, brain (more rarely), as well as cellulite, lymphadenitis and osteomyelitis [1-3, 6, 7, 12, 14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The clinical manifestations of chromobacteriosis begin after the incubation period ranging from 3 to 14 days, according to the form of exposure to the agent [1,8]. It includes inflammatory signs at the entry site, associated with fever, nausea, vomiting, abdominal pain [1,3,4] with rapid evolution to sepsis, rapid spread and high mortality [2,3,12,13]. There is formation of multiple abscesses in the lung, liver, spleen, brain (more rarely), as well as cellulite, lymphadenitis and osteomyelitis [1-3, 6, 7, 12, 14].…”
Section: Discussionmentioning
confidence: 99%
“…The Chromobacterium violaceum is a bacillus or coco-bacillus-shaped bacterium which is Gram-negative, facultative anaerobic, and usually lives in water or soil in tropical and subtropical regions [1][2][3][4][5] The most striking feature of this type of bacteria is the production of a pigment called violacein, colouring the colonies violet. However, 9% of the isolated strains do not have pigments [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infections in humans are rare, however, but when they occur, the mortality is high (MANJUNATH, 2007). Some studies have reported isolated cases in Brazil (MARTINEZ et al, 2000;DIAS et al, 2005) and abroad (LEE et al, 1999;TEOH et al, 2006). The aim of this study was to report the characterization of C. violaceum when isolated in a Neotropical aquatic environment, in association with the cultivation of Jaú.…”
Section: Introductionmentioning
confidence: 99%